Autophagy in graves’ ophthalmopathy - Chen, Yu-Qing; Gao, Lian-Di; Liu, Yi-Lin; Shen, Ya; Diao, Jia-Le; Yang, Wei-Hua; Wei, Rui-Li (Frontiers in Cell and Developmental Biology, 2023)
Graves’ ophthalmopathy (GO) is an inflammatory autoimmune disease that affects the eyes. It can significantly alter the quality of life in patients because of its distinctive pathological appearance and the effect on vision. To date, the exact pathological mechanism of GO has not been explicitly discovered. However, several studies have associated autophagy with this disease. Autophagy is a catabolic process that helps maintain homeostasis in all organisms by protecting the cells and tissues from various endogenous and exogenous stress factors. Based on our results, patients affected with GO have comparatively elevated levels of autophagy, which critically affects the pathological mechanism of the GO. In this review, we have summarized the autophagy mechanism in the pathogenesis of GO.